Composite negative electrode material and preparation method thereof, negative electrode plate, secondary battery and electric device
By introducing porous carbon and nanosilicon cores into the silicon-carbon anode material and forming a carbon cladding layer on its surface, the problem of low first efficiency of existing silicon-carbon anode materials is solved, and the structural stability and cycling performance of the material are significantly improved.
Patent Information
- Application Number
- CN202411874414.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The first effect of existing silicon-carbon anode materials is not high enough, resulting in large volume changes in lithium-ion batteries during charging and discharging, and poor structural stability, which limits the further development of the materials.
A composite negative electrode material is used, including a core and a cladding layer. The core consists of porous carbon and nanosilicon loaded on the porous carbon. The lithium element is distributed between the core and the cladding layer, and a carbon cladding layer is formed by vapor deposition technology.
It effectively improves the first effect of silicon-carbon negative electrode material, enhances the structural stability and cycling performance of the material, reduces lithium ion losses, and improves the overall performance of the battery.
Smart Images

Figure CN119890253A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary batteries, and in particular to a composite negative electrode material and a preparation method thereof, a negative electrode sheet, a secondary battery and an electrical device. Background Art
[0002] At present, the negative electrode material of lithium-ion batteries mainly uses traditional graphite materials. However, due to its significant specific capacity advantage, silicon-based materials are gradually increasing their proportion in negative electrode materials. Silicon-based negative electrode materials are mainly divided into two technical routes: silicon-oxygen and silicon-carbon. Among them, silicon-carbon negative electrode materials are a composite of nano-silicon and graphite. This material utilizes the high specific capacity characteristics of nano-silicon. At the same time, through the composite with graphite, it can alleviate the volume change of silicon during the charging and discharging process to a certain extent, and improve the structural stability and cycle performance of the material.
[0003] The silicon-carbon prepared by the existing technology has a low first efficiency of the carbon matrix, which results in a low first efficiency of silicon-carbon and a loss of cathode capacity. As the requirements for ED become higher and higher, high first efficiency deposited silicon-carbon materials are becoming more and more competitive. If the silicon content is forcibly increased to improve the first efficiency, the expansion will increase and the material will be more likely to fail during use. The first efficiency problem of negative electrode materials is a key issue in lithium-ion batteries, and it is also a bottleneck that restricts the further development of current materials.
[0004] In view of this, there is an urgent need to develop a composite negative electrode material that can effectively improve the initial efficiency of silicon-carbon negative electrode materials. Summary of the invention
[0005] The purpose of the present invention is to provide a composite negative electrode material to effectively improve the initial effect of silicon-carbon negative electrode materials in view of the deficiencies in the prior art.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] A composite negative electrode material comprises a core and a coating layer coated on the outer surface of the core, wherein the core comprises porous carbon and nano-silicon loaded on the porous carbon, and lithium is distributed between the core and the coating layer.
[0008] Preferably, the particle size D50 of the porous carbon is R1 μm, the particle size D50 of the nano-silicon particles is R2 nm, and the content of the nano-silicon is B% of the mass of the silicon-carbon, wherein 2.8<(R1-R2)×B%<3.5. When the value of the relationship (R1-R2)×B% is too small, the material's initial efficiency will be low, the cathode's gram capacity will be low, and the cost of the battery cell will increase; when the value of the relationship (R1-R2)×B% is too large, the material will expand greatly, the stress will be large during expansion, the porous carbon matrix will be severely damaged, and the material will be more prone to pulverization and failure.
[0009] Preferably, the coating layer is a carbon coating layer.
[0010] Preferably, the particle size D50 of the porous carbon is 7-9 μm. If the particle size is too small, the yield will be low and the cost will increase. If the particle size is too large, the diffusion resistance of lithium ions in the particles will be large and the rate performance will be poor.
[0011] Preferably, the particle size D50 of the nano silicon particles is 1-3 nm. If the particle size of the nano silicon is too small, there will be more interfaces between silicon and carbon, more lithium ion transfer interfaces, greater impedance, and greater polarization of the material during use. If the size of the nano silicon is too large, the uniformity of lithium insertion inside the silicon will be worse, it will be easier to break, and the expansion degree will increase.
[0012] Preferably, the pore volume of the porous carbon is 0.6-1.0 cm 3 / g, the pore distribution structure is: micropores account for 80-90%, mesopores account for 8-15%, and macropores account for 1-5%, among which the pore size of micropores is ≤2nm, the pore size of mesopores is 2-50nm, and the pore size of macropores is ≥50nm.
[0013] In addition, the present invention also provides a method for preparing a composite negative electrode material, comprising the following steps:
[0014] S1, carbonizing the carbon source under the protection of an inert gas to obtain a carbon matrix;
[0015] S2, forming pores in the carbon matrix and purifying the carbon matrix to obtain a porous carbon matrix;
[0016] S3, vapor-depositing silicon on the porous carbon substrate to obtain the core;
[0017] S4, vapor-depositing lithium on the core to obtain a core with lithium distributed on the surface;
[0018] S5. Vapor-depositing carbon on the inner core obtained in S4 to form a carbon coating layer to obtain the composite negative electrode material.
[0019] Preferably, the carbonization of S1 comprises carbonizing the carbon source at 900-1200° C. for 3-6 hours.
[0020] Preferably, in step S1, the carbon source is obtained by carbonizing biomass such as coconut shell, rice husk, platycodon, or phenolic resin-based carbon source, epoxy resin-based carbon source, petroleum coke, anthracite, etc. Among them, the resin-based carbon source is conducive to improving the structural stability of the material and enhancing the pressure resistance of the material.
[0021] Among them, in step S1, if the temperature and reaction time are lower than the preset range, the carbon source cannot be better carbonized, there are too many heteroatoms, and the initial efficiency of the material is low. If the temperature and reaction time are higher than the preset range, the obtained carbon source structure will be loose, the structural stability is poor, and the material pressure resistance is poor. Controlling the temperature and reaction time within the preset range can reduce the heteroatoms while enhancing the stability of the formed carbon structure, so that the material can ensure the optimal structural stability and initial efficiency of the material. The role of introducing inert gas is to isolate the oxygen in the air and protect the carbon matrix.
[0022] Preferably, the pore-forming of S2 comprises mixing a carbon matrix with a pore-forming agent and calcining at 850-1000° C. for 1-2 hours.
[0023] Preferably, the purification of S2 comprises acid washing and water washing the calcined product to neutrality, and then calcining at 500-600° C. for 3-4 hours.
[0024] Preferably, the pore-forming agent of S2 is an alkaline pore-forming agent.
[0025] Preferably, the pore-forming agent includes at least one of sodium hydroxide and potassium hydroxide.
[0026] Preferably, the concentration of the pore-forming agent is 1-2 mol / L.
[0027] Preferably, the added amount of the pore former is 8%-15% of the mass of the carbon matrix.
[0028] Among them, in step S2, a large amount of impurities and heteroatoms will be generated during the pore-forming process, so the product needs to be purified by acid dissolution and the excess residual alkali needs to be washed and neutralized. If the reaction time is too short, the heteroatom content will be high, and if the reaction time is too long, the porous carbon structure will be unstable. The carbon matrix is purified by high-temperature heating, the heteroatom content is reduced, especially the content of oxygen atoms (<2%), and the initial effect of the material in battery applications is improved.
[0029] Preferably, the vapor deposition of silicon in S3 comprises placing a porous carbon substrate in a reaction device, introducing a first mixed gas containing a first protective gas and a silicon source gas, and vapor depositing silicon on the porous carbon substrate.
[0030] Preferably, the vapor deposition conditions of silicon are 350-450° C. and the deposition time is 1-3 hours.
[0031] Preferably, the content of the first protective gas is 10%-30% of the volume of the first mixed gas; preferably, the silicon source gas includes silane gas.
[0032] Preferably, the first protective gas includes at least one of helium, nitrogen, argon and krypton. Wherein, silane gas is introduced into the porous carbon and reduced to nano-silicon, and the nano-silicon grows in the porous carbon, and the size is subject to the pore size of the porous carbon and the reaction temperature and time. If the reaction temperature is too low, silane is difficult to be reduced and the production capacity is low. If the reaction temperature is too high, nano-silicon will be converted from amorphous silicon to crystalline silicon, resulting in expansion anisotropy, increasing the expansion rate of the material and easily generating chemically inert silicon carbide. If the reaction time is too short, silicon cannot be completely deposited inside, and if the reaction time is too long, silicon is easily accumulated on the surface, increasing the expansion of the material and shortening the service life.
[0033] Preferably, the vapor-deposited lithium of S4 includes passing a second mixed gas containing a second protective gas and a carbon source gas into an organic lithium solution, heating the solution to obtain an organic lithium gas, and then passing the organic lithium gas into a reaction device containing the inner core, vapor-depositing lithium on the inner core to obtain an inner core having lithium element distributed on its surface.
[0034] Preferably, the heating reaction condition of S4 is 300-400° C. for 1-3 h.
[0035] Preferably, the organic lithium solution is at least one of n-butyl lithium, lithium methoxide, sec-butyl lithium and lithium diisopropylamide.
[0036] Preferably, the carbon source gas of S4 includes at least one of acetylene, ethylene and methane.
[0037] Preferably, the flow rate of the organic lithium gas is 0.1-0.3 m / s.
[0038] Preferably, the second protective gas includes at least one of helium, nitrogen, argon and krypton.
[0039] Wherein, in step S4, lithium is supplemented by vapor deposition, which greatly improves the uniformity of lithium supplementation compared to solid-phase and liquid-phase mixed lithium supplementation, and the amount of lithium supplementation can be controlled by controlling the mixed gas flow rate. Organic gas and inert gas are introduced into a volatile organic lithium solution, so that the organic lithium is reduced and distributed on the surface of the particles to achieve lithium supplementation. The lithium element is located on the outside of the silicon-carbon material, which effectively compensates for the loss of lithium ions caused by the formation of the solid electrolyte interface (SEI) film during the cycle of the battery, and can effectively improve the first effect of the silicon-carbon negative electrode material. When the reaction temperature is too low, it will cause incomplete decomposition of organic lithium and low lithium supplementation efficiency. When the reaction temperature is too high, it will cause amorphous silicon to become crystalline silicon, and the expansion and dynamic performance of crystalline silicon are not as good as amorphous silicon. When the reaction time is too low, it will cause incomplete decomposition of organic lithium and low lithium supplementation efficiency. When the reaction time is too high, it will cause amorphous silicon to become crystalline silicon, and the expansion and dynamic performance of crystalline silicon are not as good as amorphous silicon. When the organic lithium gas flow rate is too low, it will cause insufficient reservation. When the organic lithium gas flow rate is too high, it will cause the fluidized state to be unstable and the pre-lithium is uneven.
[0040] Preferably, the vapor-depositing carbon in S5 comprises introducing a carbon source gas into a reaction device containing the inner core obtained in S4, and vapor-depositing carbon on the inner core.
[0041] Preferably, the carbon source gas of S5 includes acetylene.
[0042] Preferably, the vapor phase carbon deposition conditions are 550-600° C. and deposition time is 1-3 h.
[0043] If the deposition temperature is too high, chemically inert silicon carbide is easily generated. If the deposition temperature is too low, organic gas and organic lithium are difficult to be reduced. If the reaction time is too short, the organic gas will not react fully, and the obtained coated carbon layer will contain impurity atoms, which will reduce the initial efficiency of the material. If the reaction time is too long, the amorphous silicon in the silicon-carbon material will turn into crystalline silicon, and the expansion and dynamic properties of crystalline silicon are worse than those of amorphous silicon.
[0044] In addition, the present invention also provides a negative electrode sheet, comprising the above-mentioned composite negative electrode material.
[0045] In addition, the present invention also provides a secondary battery, including a battery cell formed by winding a negative electrode sheet, a positive electrode sheet and a separator, an electrolyte, and a shell that encapsulates the battery cell and the electrolyte, wherein the negative electrode sheet is the above-mentioned negative electrode sheet.
[0046] In addition, the present invention also provides an electrical device, comprising the secondary battery.
[0047] Compared with the prior art, the beneficial effect of the present invention is that the present invention reduces the organic lithium and distributes it on the surface of the particles to achieve lithium replenishment by passing organic gas and inert gas into the volatile organic lithium solution. The lithium element is located on the outside of the silicon-carbon material, which effectively compensates for the loss of lithium ions caused by the formation of the solid electrolyte interface (SEI) film during the battery cycle, and can effectively improve the first effect of the silicon-carbon negative electrode material. In addition, the lithium element is wrapped by the carbon material, which significantly improves its chemical stability in the air. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 Schematic diagram of the structure of a composite negative electrode material according to an embodiment of the present invention.
[0049] Among them, 1-pores; 2-porous carbon; 3-lithium particles; 4-carbon coating layer. DETAILED DESCRIPTION
[0050] In order to make the technical solutions and advantages of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0051] According to the first aspect of the present application, the present application provides a composite negative electrode material, including a core and a coating layer coated on the outer surface of the core, the core including porous carbon and nano-silicon loaded on the porous carbon, and lithium is distributed between the core and the coating layer.
[0052] In some embodiments, the particle size D50 of the porous carbon is R1 μm, the particle size D50 of the nano-silicon particles is R2 nm, and the content of the nano-silicon is B% of the mass of the silicon carbon, wherein 2.8<(R1-R2)×B%<3.5, for example, it can be 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, etc.
[0053] In some embodiments, the coating is a carbon coating.
[0054] In some embodiments, the particle size D50 of the porous carbon is 7-9 μm, for example, 7 μm, 8 μm, or 9 μm.
[0055] In some embodiments, the particle size D50 of the nano-silicon particles is 1-3 nm, for example, 1.5 nm, 2 nm, or 2.2 nm.
[0056] In some embodiments, the pore volume of the porous carbon is 0.6-1.0 cm 3 / g, for example, 0.6 cm3 / g, 0.7cm 3 / g, 0.8cm 3 / g, 0.9cm 3 / g, 1.0cm 3 / g; the pore distribution structure is: micropores account for 80-90%, mesopores account for 8-15%, and macropores account for 1-5%, among which the pore size of micropores is ≤2nm, the pore size of mesopores is 2-50nm, and the pore size of macropores is ≥50nm.
[0057] According to a second aspect of the present application, the present application provides a method for preparing a composite negative electrode material, comprising the following steps:
[0058] S1, carbonizing the carbon source under the protection of an inert gas to obtain a carbon matrix;
[0059] S2, forming pores in the carbon matrix and purifying the carbon matrix to obtain a porous carbon matrix;
[0060] S3, vapor-depositing silicon on the porous carbon substrate to obtain the core;
[0061] S4, vapor-depositing lithium on the core to obtain a core with lithium distributed on the surface;
[0062] S5. Vapor-depositing carbon on the inner core obtained in S4 to form a carbon coating layer to obtain the composite negative electrode material.
[0063] In some embodiments, the carbonization of step S1 includes carbonizing the carbon source at 900-1200°C for 3-6 hours. The carbonization temperature may be, for example, 900°C, 1000°C, 1100°C, 1200°C, and the carbonization time may be, for example, 3 hours, 4 hours, 5 hours, 6 hours.
[0064] In some embodiments, in step S1, the carbon source is obtained by carbonizing biomass such as coconut shells, rice husks, platycodon grandiflorum, or phenolic resin-based carbon sources, epoxy resin-based carbon sources, petroleum coke, anthracite, and the like.
[0065] In some embodiments, the pore formation of S2 includes mixing a carbon matrix with a pore-forming agent and calcining at 850-1000°C for 1-2h. The calcination temperature can be, for example, 850°C, 900°C, 950°C, 1000°C, and the calcination time can be, for example, 1h, 1.5h, 2h.
[0066] In some embodiments, the purification of S2 includes acid washing and water washing to neutrality of the calcined product, and then calcining at 500-600° C. for 3-4 hours and crushing. The calcination temperature can be, for example, 500° C., 550° C., 600° C., and the calcination time can be, for example, 3 hours, 3.5 hours, or 4 hours.
[0067] In some embodiments, the pore former of S2 is a basic pore former.
[0068] In some embodiments, the pore former includes at least one of sodium hydroxide and potassium hydroxide.
[0069] In some embodiments, the concentration of the pore-forming agent is 1-2 mol / L, for example, 1 mol / L or 2 mol / L.
[0070] In some embodiments, the amount of the pore former added is 8%-15% of the mass of the carbon matrix, for example, 8%, 9%, 10%, 11%, 12%, 13%, 14%, or 15%.
[0071] In some embodiments, the vapor-depositing silicon in S3 includes placing a porous carbon substrate in a reaction device, introducing a first mixed gas containing a first protective gas and a silicon source gas, and vapor-depositing silicon on the porous carbon substrate.
[0072] In some embodiments, the vapor deposition conditions of silicon are 350-450° C., such as 350° C., 400° C., or 450° C., and the deposition time is 1-3 h, such as 1 h, 1.5 h, 2 h, or 3 h.
[0073] In some embodiments, the content of the first protective gas is 10%-30% of the volume of the first mixed gas, for example, it can be 10%, 15%, 20%, 25%, or 30%.
[0074] In some embodiments, the silicon source gas includes silane gas; preferably, the first protective gas includes at least one of helium, nitrogen, argon and krypton.
[0075] In some embodiments, the vapor-deposited lithium of S4 includes passing a second mixed gas containing a second protective gas and a carbon source gas into an organic lithium solution, heating the reaction to obtain an organic lithium gas, and then passing the organic lithium gas into a reaction device equipped with the core, vapor-depositing lithium on the core to obtain a core with lithium element distributed on the surface.
[0076] In some embodiments, the heating reaction conditions of S4 are 300-400°C, for example, 300°C, 350°C, 400°C; the reaction time is 1-3h, for example, 1h, 1.5h, 2h, 3h.
[0077] In some embodiments, the organic lithium solution is at least one of n-butyl lithium, lithium methoxide, sec-butyl lithium, and lithium diisopropylamide.
[0078] In some embodiments, the carbon source gas of S4 includes at least one of acetylene, ethylene, and methane.
[0079] In some embodiments, the flow rate of the organic lithium gas is 0.1-0.3 m / s, for example, 0.1 m / s, 0.2 m / s, or 0.3 m / s.
[0080] In some embodiments, the second shielding gas includes at least one of helium, nitrogen, argon, and krypton.
[0081] In some embodiments, the vapor-depositing carbon in S5 comprises introducing a carbon source gas into a reaction device containing the inner core obtained in S4, and vapor-depositing carbon on the inner core.
[0082] In some embodiments, the carbon source gas of S5 includes acetylene.
[0083] In some embodiments, the vapor deposition carbon is performed at 550-600°C, such as 550°C, 580°C, or 600°C, for 1-3 hours, such as 1 hour, 1.5 hours, 2 hours, or 3 hours.
[0084] According to a third aspect of the present application, the present application provides a negative electrode sheet, comprising a negative electrode current collector and a negative electrode active material layer coated on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer comprises the above-mentioned composite negative electrode material.
[0085] According to the fourth aspect of the present application, the present application provides a secondary battery, including a battery cell formed by winding a negative electrode sheet, a positive electrode sheet and a separator, an electrolyte, and a shell that encapsulates the battery cell and the electrolyte, wherein the negative electrode sheet is the above-mentioned negative electrode sheet.
[0086] According to a fifth aspect of the present application, the present application provides an electrical device comprising the above-mentioned secondary battery.
[0087] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector. The positive electrode active material layer includes a positive electrode active material. The positive electrode active material may include but is not limited to a chemical formula such as Li a Ni x Co y M z O 2-b N b (wherein 0.95≤a≤1.2, x>0, y≥0, z≥0, and x+y+z=1, 0≤b≤1, M is selected from a combination of one or more of Mn and Al, and N is selected from a combination of one or more of F, P, and S) The positive electrode active material may also be, but is not limited to, LiCoO2, LiNiO2, LiVO2, LiCrO2, LiMn2O4, LiCoMnO4, Li2NiMn3O8, LiNi 0.5 Mn 1.5O4, LiCoPO4, LiMnPO4, LiFePO4, LiNiPO4, LiCoFSO4, CuS2, FeS2, MoS2, NiS, TiS2, etc. The positive active material may also be modified. The method of modifying the positive active material should be known to those skilled in the art. For example, the positive active material may be modified by coating, doping, etc. The material used for the modification may include but is not limited to a combination of one or more of Al, B, P, Zr, Si, Ti, Ge, Sn, Mg, Ce, W, etc. The positive current collector is usually a structure or part for collecting current. The positive current collector may be various materials suitable for use as a positive current collector for lithium-ion batteries in the art. For example, the positive current collector may include but is not limited to metal foil, etc., and more specifically may include but is not limited to aluminum foil, etc.
[0088] The separator can be any material suitable for secondary battery separators in the art, for example, it can be a combination of one or more of, but not limited to, polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester and natural fibers.
[0089] The secondary battery also includes an electrolyte, which includes an organic solvent, an electrolyte lithium salt and an additive. Among them, the electrolyte lithium salt can be LiPF6 and / or LiBOB used in high-temperature electrolytes; it can also be at least one of LiBF4, LiBOB, and LiPF6 used in low-temperature electrolytes; it can also be at least one of LiBF4, LiBOB, LiPF6, and LiTFSI used in anti-overcharge electrolytes; it can also be at least one of LiClO4, LiAsF6, LiCF3SO3, and LiN(CF3SO2)2. The organic solvent can be a cyclic carbonate, including PC and EC; it can also be a chain carbonate, including DFC, DMC, or EMC; it can also be a carboxylic acid ester, including MF, MA, EA, MP, etc. The additives include but are not limited to at least one of film-forming additives, conductive additives, flame retardant additives, anti-overcharge additives, additives for controlling the content of H2O and HF in the electrolyte, additives for improving low-temperature performance, and multifunctional additives.
[0090] The present invention will be described in further detail below in conjunction with specific implementation modes, but the implementation modes of the present invention are not limited thereto.
[0091] Example 1
[0092] Negative electrode material preparation:
[0093] like Figure 1As shown, a composite negative electrode material provided in this embodiment includes a core 2 and a coating layer 4 coated on the outer surface of the core 2, wherein the core 2 includes porous carbon and nano-silicon loaded on the porous carbon, and a lithium element 3 is distributed between the core 2 and the coating layer 4.
[0094] The method for preparing the composite negative electrode material comprises the following steps:
[0095] S1. Place a carbon source at a temperature of 1000° C., introduce nitrogen, and heat for 3 hours to obtain a carbon matrix; wherein the carbon source is phenolic resin (purchased from Shaoguan Derui Chemical Industry Co., Ltd., CAS: 9003-35-4).
[0096] S2. Mix the carbon matrix with potassium hydroxide and place it in a constant temperature device for calcination at 850℃ for 1.5h. After the reaction is completed, acid wash it, wash it with water until it is neutral, dry it, calcine it at 500℃ for 4h, and crush it to obtain a porous carbon matrix; wherein the concentration of potassium hydroxide is 1mol / L, and the amount of potassium hydroxide added accounts for 9% of the mass of the carbon matrix. The pore volume of the porous carbon matrix is 0.8cm 3 / g, the particle size D50 is 8.5μm, and the pore distribution accounts for 85% micropores, 10% mesopores and 5% macropores.
[0097] S3. Place the porous carbon matrix in a rotary kiln, introduce the first mixed gas into it for reaction, and obtain a porous carbon matrix with nano-silicon deposited thereon; wherein the first mixed gas is a mixed gas of nitrogen and silane, the volume of nitrogen accounts for 25% of the volume of the first mixed gas, the reaction temperature is 400°C, and the reaction time is 2h.
[0098] S4. Place the porous carbon substrate deposited with nano-silicon in a rotary furnace, pass the second mixed gas into the organic lithium solution to heat and react to obtain organic lithium gas, and then pass the organic lithium gas into the rotary furnace for reaction; wherein the second mixed gas is a mixed gas of nitrogen and acetylene (the volume ratio of nitrogen and acetylene is 1:3), the organic lithium solution is n-butyl lithium, the reaction temperature is 360°C, the reaction time is 2h, and the gas flow rate is 0.2m / s.
[0099] S5. After the reaction is complete, stop introducing the organic lithium gas, and then introduce the organic gas to react. After the reaction is completed, the composite negative electrode material is obtained; wherein the organic gas is acetylene, the reaction temperature is 550° C., and the reaction time is 2 h.
[0100] The particle size D50 of the porous carbon is 8.5 μm, the particle size D50 of the nano-silicon particles is 1.8 nm, and the content of the nano-silicon is 46% of the mass of the silicon-carbon.
[0101] Example 2
[0102] Different from Example 1, in step S4 of this example, the air flow rate is 0.2 m / s, the reaction temperature is 300° C., and the reaction time is 1 hour.
[0103] The rest is the same as Example 1 and will not be described again here.
[0104] Example 3
[0105] Different from Example 1, in step S4 of this example, the air flow rate is 0.3 m / s, the reaction temperature is 300° C., and the reaction time is 1 hour.
[0106] The rest is the same as Example 1 and will not be described again here.
[0107] Example 4
[0108] Different from Example 1, in step S4 of this example, the air flow rate is 0.2 m / s, the reaction temperature is 360° C., and the reaction time is 1 hour.
[0109] The rest is the same as Example 1 and will not be described again here.
[0110] Example 5
[0111] Different from Example 1, in step S4 of this example, the air flow rate is 0.1 m / s, the reaction temperature is 300° C., and the reaction time is 1 hour.
[0112] The rest is the same as Example 1 and will not be described again here.
[0113] Example 6
[0114] Different from Example 1, in step S4 of this example, the air flow rate is 0.2 m / s, the reaction temperature is 360° C., and the reaction time is 3 hours.
[0115] The rest is the same as Example 1 and will not be described again here.
[0116] Example 7
[0117] Different from Example 1, in step S4 of this example, the air flow rate is 0.2 m / s, the reaction temperature is 400° C., and the reaction time is 1 hour.
[0118] The rest is the same as Example 1 and will not be described again here.
[0119] Comparative Example 1
[0120] Different from Example 1, in step S4 of this comparative example, the mixed gas does not pass through the organic lithium solution, the gas flow rate is 0.2 m / s, the reaction temperature is 400° C., the reaction time is 1 hour, and the reaction time in step S5 is 1 hour.
[0121] The rest is the same as Example 1 and will not be described again here.
[0122] Comparative Example 2
[0123] Different from Example 1, in step S4 of this comparative example, the mixed gas does not pass through the organic lithium solution, the gas flow rate is 0.2 m / s, the reaction temperature is 400° C., the reaction time is 2 hours, and the reaction time in step S5 is 2 hours.
[0124] The rest is the same as Example 1 and will not be described again here.
[0125] Comparative Example 3
[0126] Different from Example 1, the reaction temperature in step S4 of this comparative example is 200°C.
[0127] The rest is the same as that of Example 1 and will not be described again here.
[0128] Comparative Example 4
[0129] Different from Example 1, the reaction temperature in step S4 of this comparative example is 500°C.
[0130] The rest is the same as that of Example 1 and will not be described again here.
[0131] Comparative Example 5
[0132] Different from Example 1, the reaction time in step S4 of this comparative example is 0.5 hour and the air flow rate is 0.1 m / s.
[0133] The rest is the same as that of Example 1 and will not be described again here.
[0134] Comparative Example 6
[0135] Different from Example 1, the reaction time in step S4 of this comparative example is 4 hours and the air flow rate is 0.1 m / s.
[0136] The rest is the same as that of Example 1 and will not be described again here.
[0137] Comparative Example 7
[0138] Different from Example 1, the flow rate of the organic lithium gas in step S4 of this comparative example is 0.5 m / s.
[0139] The rest is the same as that of Example 1 and will not be described again here.
[0140] Comparative Example 8
[0141] Different from Example 1, the carbon coating reaction time in step S5 of this comparative example is 4 hours.
[0142] The rest is the same as that of Example 1 and will not be described again here.
[0143] Comparative Example 9
[0144] Different from Example 1, in step S2 of this comparative example, no purification treatment is performed after pore formation (ie, no water washing and calcination treatment is performed).
[0145] The rest is the same as that of Example 1 and will not be described again here.
[0146] Comparative Example 10
[0147] Different from Example 1, the preparation process of the composite negative electrode material in this comparative example does not include step S5.
[0148] The rest is the same as that of Example 1 and will not be described again here.
[0149] The negative electrode materials of the above embodiments and comparative examples are further applied to the preparation of lithium ion batteries, and the specific preparation method includes:
[0150] S1. Preparation of positive electrode sheet: Mix the positive electrode active material lithium cobalt oxide, the conductive agent conductive carbon black, and the binder polyvinylidene fluoride in a mass ratio of 97:1.5:1.5, add N-methylpyrrolidone (NMP), and stir evenly under the action of a vacuum mixer to obtain a positive electrode slurry, wherein the solid content of the positive electrode slurry is 75wt%. The positive electrode slurry is evenly coated on one surface of an aluminum foil with a thickness of 8μm, and the aluminum foil is dried at 125°C for 1h to obtain a positive electrode sheet coated with a positive electrode material layer on one side. Repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode sheet coated with a positive electrode material layer on both sides. Then, after cold pressing, cutting, and slitting, dry under vacuum conditions at 125°C for 2h to obtain a positive electrode with a specification of 65mm×860mm.
[0151] S2. Preparation of negative electrode sheet: negative electrode material, CMC, PAA and CNT are mixed in a mass ratio of negative electrode material: CMC: PAA: CNT = 80:9:10:1, deionized water is added, and the mixture is stirred evenly under the action of a vacuum mixer to obtain a negative electrode slurry, wherein the solid content of the negative electrode slurry is 45wt%. The negative electrode slurry is evenly coated on one surface of a copper foil with a thickness of 6μm, and the copper foil is dried at 120°C to obtain a negative electrode coated with a negative electrode material layer on one side. Repeat the above steps on the other surface of the aluminum foil to obtain a negative electrode coated with a negative electrode material layer on both sides. Then, after cold pressing, cutting and slitting, it is dried under vacuum conditions at 120°C for 2h to obtain a negative electrode with a specification of 69mm×868mm.
[0152] S3. Preparation of electrolyte: In an argon atmosphere glove box with a water content of <10 ppm, EC, PC and DMC are mixed in a mass ratio of 3:2:4 to obtain an organic solvent, and then lithium hexafluorophosphate is added to the organic solvent to obtain an electrolyte, wherein the concentration of the lithium salt is 1 mol / L.
[0153] S4, assembly of lithium-ion battery: stack the positive electrode, separator (PE), and negative electrode prepared above in order, place the separator between the positive electrode and the negative electrode to play a role of isolation, and wind to obtain an electrode assembly. Place the electrode assembly in an aluminum-plastic film packaging bag, inject electrolyte after drying, and obtain a lithium-ion battery through vacuum packaging, standing, formation, degassing, trimming and other processes.
[0154] Performance Testing
[0155] The capacity and first efficiency test steps are: 0.1C discharge to 0.05V, leave for 5 minutes, 0.01C discharge to 0.05V, leave for 5 minutes, 0.1C charge to 1.5V, leave for 5 minutes.
[0156] The test results are shown in Table 1.
[0157] Table 1
[0158]
[0159]
[0160] Note: The more carbon coating, the longer the carbon coating time, the less likely the material will produce gas during the stirring and coating process, which is beneficial to improving the processing performance of the material. However, the more carbon coating, the longer the carbon coating time, the lower the capacity and initial efficiency of the material.
[0161] From the comparison of the experimental data of Examples 1-7 and Comparative Examples 1-10 in Table 1, it can be seen that the present application achieves lithium replenishment by introducing organic gas and inert gas into a volatile organic lithium solution, so that the organic lithium is reduced and distributed on the surface of the particles. The lithium element is located on the outside of the silicon-carbon material, which effectively compensates for the loss of lithium ions caused by the formation of the solid electrolyte interface (SEI) film during the battery cycle, and can effectively improve the first efficiency and capacity of the silicon-carbon negative electrode material. In addition, the lithium element is also wrapped by the carbon material, which significantly improves its chemical stability in the air.
[0162] Among them, through the comparison of the data of Example 1 and Comparative Examples 1-2, it can be obtained that when lithium is not supplemented, the initial efficiency and capacity of the prepared conventional silicon-carbon material are relatively low. Through the comparison of the data of Example 1 and Comparative Examples 3-6, it can be obtained that the length of the lithium supplement time and the temperature have a certain influence on the performance of the material. When the lithium supplement time is too long, it will cause amorphous silicon to become crystalline silicon, and the expansion and dynamic properties of crystalline silicon are not as good as amorphous silicon. When the lithium supplement time is too short, the lithium supplement efficiency is low; when the lithium supplement temperature is too high, it will cause amorphous silicon to become crystalline silicon, and the expansion and dynamic properties of crystalline silicon are not as good as amorphous silicon. When the lithium supplement temperature is too low, the organic lithium is not completely decomposed, and the lithium supplement efficiency is low. Through the comparison of the data of Example 1 and Comparative Example 7, it can be obtained that when the flow rate of the organic lithium gas is too large, it will cause the fluidized state to be unstable and the pre-lithium to be uneven.
[0163] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.
Claims
1. A composite negative electrode material, characterized in that: It comprises a core and a coating layer coated on the outer surface of the core, wherein the core comprises porous carbon and nano silicon loaded on the porous carbon, and lithium single substance is distributed between the core and the coating layer.
2. A composite negative electrode material according to claim 1, characterized in that: The particle size D50 of the porous carbon is R1 μm, the particle size D50 of the nano-silicon particles is R2 nm, and the content of the nano-silicon is B% of the mass of the silicon-carbon, wherein 2.8<(R1-R2)×B%<3.
5.
3. A composite negative electrode material according to claim 1, characterized in that: The coating layer is a carbon coating layer.
4. A composite negative electrode material according to claim 1, characterized in that: The particle size D50 of the porous carbon is 7-9 μm, and the particle size D50 of the nano silicon particles is 1-3 nm.
5. A composite negative electrode material according to claim 1, characterized in that: The pore volume of the porous carbon is 0.6-1.0 cm 3 / g, the pore distribution structure is: micropores account for 80-90%, mesopores account for 8-15%, and macropores account for 1-5%, among which the pore size of micropores is ≤2nm, the pore size of mesopores is 2-50nm, and the pore size of macropores is ≥50nm.
6. A method for preparing a composite negative electrode material according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1, carbonizing the carbon source under the protection of an inert gas to obtain a carbon matrix; S2, forming pores in the carbon matrix and purifying the carbon matrix to obtain a porous carbon matrix; S3, vapor-depositing silicon on the porous carbon substrate to obtain the core; S4, vapor-depositing lithium on the core to obtain a core with lithium element distributed on the surface; S5. Vapor-depositing carbon on the inner core obtained in S4 to form a carbon coating layer to obtain the composite negative electrode material.
7. The method for preparing a composite negative electrode material according to claim 6, characterized in that: The carbonization of S1 comprises carbonizing the carbon source at 900-1200° C. for 3-6 hours; And / or, the pore-forming of S2 comprises mixing a carbon matrix with a pore-forming agent, and calcining at 850-1000°C for 1-2h; preferably, the purification of S2 comprises acid washing and water washing the calcined product to neutrality, and then calcining at 500-600°C for 3-4h; preferably, the pore-forming agent is an alkaline pore-forming agent; preferably, the pore-forming agent comprises at least one of sodium hydroxide and potassium hydroxide; preferably, the concentration of the pore-forming agent is 1-2mol / L; preferably, the amount of the pore-forming agent added is 8%-15% of the mass of the carbon matrix; And / or, the vapor deposition of silicon in S3 comprises placing a porous carbon substrate in a reaction device, introducing a first mixed gas containing a first protective gas and a silicon source gas, and vapor depositing silicon on the porous carbon substrate; preferably, the vapor deposition of silicon is carried out under conditions of 350-450° C. for 1-3 hours; preferably, the content of the first protective gas is 10%-30% of the volume of the first mixed gas; preferably, the silicon source gas comprises silane gas; preferably, the first protective gas comprises at least one of helium, nitrogen, argon and krypton; And / or, the vapor-deposited lithium of S4 comprises passing a second mixed gas containing a second protective gas and a carbon source gas into an organic lithium solution, heating the mixture to obtain an organic lithium gas, and then passing the organic lithium gas into a reaction device equipped with the inner core, vapor-depositing lithium on the inner core to obtain an inner core with lithium element distributed on the surface; preferably, the heating reaction conditions of S4 are 300-400°C for 1-3h; preferably, the organic lithium solution is at least one of n-butyl lithium, lithium methoxide, sec-butyl lithium and lithium diisopropylamide; preferably, the carbon source gas of S4 comprises at least one of acetylene, ethylene and methane; preferably, the flow rate of the organic lithium gas is 0.1-0.3m / s; preferably, the second protective gas comprises at least one of helium, nitrogen, argon and krypton; And / or, the vapor-deposited carbon of S5 includes passing a carbon source gas into a reaction device containing the inner core obtained in S4, and vapor-depositing carbon on the inner core; preferably, the carbon source gas of S5 includes acetylene; preferably, the conditions for the vapor-deposited carbon are deposition at 550-600°C for 1-3h.
8. A negative electrode sheet, characterized in that: The composite negative electrode material comprises the composite negative electrode material according to any one of claims 1 to 5.
9. A secondary battery, characterized in that: Includes the negative electrode sheet as described in claim 8.
10. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to claim 9.
Citation Information
Patent Citations
Silicon-carbon negative electrode material for lithium ion battery and preparation method of silicon-carbon negative electrode material
CN111755681A
Lithium ion battery electrode material and preparation method thereof
CN112909224A
Lithium metal composite material and modified material thereof, and preparation methods and applications of lithium metal composite material and modified material
CN114944470A
Silicon-carbon negative electrode material and preparation method thereof, electrode plate and lithium ion battery
CN118693264A
Method of producing negative electrode material
JP2018152162A
Cited By
Silicon-carbon composite negative electrode material for lithium ion battery and preparation method of silicon-carbon composite negative electrode material
CN120109182A